2008
DOI: 10.1590/1809-9823.2008.11025
|View full text |Cite
|
Sign up to set email alerts
|

Equilíbrio e marcha de idosos residentes em instituições asilares do município de Catanduva, SP

Abstract: RESUMO O presente trabalho tem como objetivos avaliar o equilíbrio e marcha de idosos institucionalizados e caracterizar os idosos que se apresentaram com alterações no equilíbrio e marcha segundo sexo, faixa etária, estados visual e auditivo. Este estudo, do tipo descritivo e de caráter transversal, foi realizado nas instituições asilares do município de Catanduva (SP), constituído de idosos de ambos os sexos. Os idosos foram responderam primeiramente a um questionário que trazia informações sobre identificaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
2
0
7
Order By: Relevance
“…Isso pode ser verificado na construção de calçamentos irregulares, presença de degraus, ausência de corrimão nas escadas e rampas, semáforos com tempo inadequado para a travessia, entre outros dispositivos que se fossem adequados facilitariam a vida do idoso respeitando suas limitações (16) .…”
Section: Fatoresunclassified
“…Isso pode ser verificado na construção de calçamentos irregulares, presença de degraus, ausência de corrimão nas escadas e rampas, semáforos com tempo inadequado para a travessia, entre outros dispositivos que se fossem adequados facilitariam a vida do idoso respeitando suas limitações (16) .…”
Section: Fatoresunclassified
“…They are treated as highly relevant epidemiological, social and economic factor in the whole world as it is the most common type of accident among the elderly 4 . A fall is characterized as a serious risk since it can potentially lead to complications, such as hypoactivity, social isolation, depression, institutionalization, reduces the quality of life [5][6][7] , loss of confidence, dependence in basic functional activities and even death 8 . It is noteworthy that both the incidence and severity of falls increases considerably after the sixth decade of life, tripling the rates of hospitalization of the elderly after 65 years 3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the present study, during the one-foot stance, individuals of the MAG group showed higher TD than individuals of the EG group, and the individuals of the YG group. Possibly, for the individuals of the EG, these differences were the result of effects of practice in regular physical exercises (Lojudice, 2008), therefore, improving postural stability and reducing the risk for falls (Nardone & Schieppati, 2010;Pimentel & Scheicher, 2009).…”
Section: Discussionmentioning
confidence: 99%